GERABAH SITIWINANGUN KEKAYAAN BANGSA ZAMAN PRASEJARAH YANG TAK LEKANG DI MAKAN USIA - Raditiyanto, Satria; Ghassani, Rizqi (JURNAL KEBANGSAAN RI, 2023)
No much people knows that’s a certain in the village at West Java Province Region with names the Sitiwinangun Village, Palimanan, Cirebon regency have the unique handicraft with the names Sitiwinangun handicrafts or Sitiwinangun traditional art ceramics have already started from the prehistory period till now. The Sitiwinangun traditional art ceramics its most popular into the several regions in Indonesia, even famously into China, Japan, Malaysia, Singapore, Thailand, Korea, and many other country in the world. The motive and unique the Sitiwinangun ceramics it’s very famous, and many Indonesian collectors likes to be collected. But, the results of Sitiwinangun ceramics have different qualities and quantities, and this handicraft have the unique aesthetics values too. It seems, for create the best qualities of Sitiwinangun traditional art ceramics must be have the several traditional ritualism. Because of the best qualities product, the traditional Sitiwinangun art ceramics become of the sources of the Indonesian incomes. This research is suitable with aesthetics values, promotion about the Sitiwinangun village, and surrounding, as well as the Sitiwinangun traditional art ceramics as one of the local tourist, and foreign countries tourist gifts from Cirebon, West Java province, Indonesia.